2021
DOI: 10.1002/pbc.29076
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated thyroid carcinoma in children: A retrospective analysis of 125 pediatric cases from a single institution in India

Abstract: Background: Thyroid carcinoma (TC) is extremely rare in children. We assessed the clinicopathological features, outcomes, recurrence pattern, and associated risk factors of differentiated thyroid carcinoma (DTC).Methods: Children aged ≤14 years, pathologically diagnosed as DTC at a tertiary cancer institute between January 1998 and December 2015 were retrospectively analyzed. Survival outcomes were estimated using the Kaplan-Meier method.Results: During 18 years, 125 children with DTC were treated with a male:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…DTC in the pediatric and adolescent populations represents a rare disease with a higher rate of local and distant metastatic disease compared with adult DTCs [ 117 ]. Despite the aggressive presentation [ 117 , 118 , 119 , 120 , 121 , 122 ], pediatric DTCs are the most RAI-sensitive cancers, and a cure can be achieved in up to 52% of the cases [ 121 ]. These young patients have similar recurrence rates but lower specific mortality rates than adults in studies with long follow-up periods [ 117 , 118 , 119 , 120 , 122 ], and the rare cases of cancer-related deaths occur at an adult age [ 117 ].…”
Section: Pediatric Dtcmentioning
confidence: 99%
See 1 more Smart Citation
“…DTC in the pediatric and adolescent populations represents a rare disease with a higher rate of local and distant metastatic disease compared with adult DTCs [ 117 ]. Despite the aggressive presentation [ 117 , 118 , 119 , 120 , 121 , 122 ], pediatric DTCs are the most RAI-sensitive cancers, and a cure can be achieved in up to 52% of the cases [ 121 ]. These young patients have similar recurrence rates but lower specific mortality rates than adults in studies with long follow-up periods [ 117 , 118 , 119 , 120 , 122 ], and the rare cases of cancer-related deaths occur at an adult age [ 117 ].…”
Section: Pediatric Dtcmentioning
confidence: 99%
“…The activity of RAI to be administered is calculated according to the body weight of the young patient (1–1.5 mCi/Kg) and the preferred preparation method is THW, although some experiences with rhTSH report non-inferior results [ 124 ]. Multiple RAI treatment courses are often necessary to obtain complete disease remission, and in a retrospective analysis of 125 children, 22% of patients required three or more RAI courses [ 120 ]. Considering metastatic cases, the cumulative RAI activity ranges from an average of 11.98 GBq to a maximum activity of 22.2 GBq, according to surveys [ 121 , 125 ], although Pires et al found no therapeutic benefit after 14.8 GBq of iodine administration in their cohort of 118 patients [ 126 ].…”
Section: Pediatric Dtcmentioning
confidence: 99%
“…Hypoparathyroidism is defined by a decrease in serum calcium levels and PTH: it may occur as a transient form (TtHP), with progressive normalization within six months from surgical treatment, or permanent (PtHP), whenever the patient continues to require replacement therapy 2,7–9 . Numerous reports have attempted to correlate the incidence of post‐surgical complications with the type of thyroid disease associated, positive family history of thyroid cancer, gender of the patient, type of operation, cervical lymph nodes involvement, extrathyroidal invasion, thyroiditis, surgical expertise, and surgical timing 6,10–20 . Others have investigated the possible link between the development of hypocalcemia and some biochemical parameters, like preoperative vitamin D levels, postoperative PTH, and magnesium levels and pre‐ and postoperative serum calcium levels 21–35 .…”
Section: Introductionmentioning
confidence: 99%
“…2,[7][8][9] Numerous reports have attempted to correlate the incidence of post-surgical complications with the type of thyroid disease associated, positive family history of thyroid cancer, gender of the patient, type of operation, cervical lymph nodes involvement, extrathyroidal invasion, thyroiditis, surgical expertise, and surgical timing. 6,[10][11][12][13][14][15][16][17][18][19][20] Others have investigated the possible link between the development of hypocalcemia and some biochemical parameters, like preoperative vitamin D levels, postoperative PTH, and magnesium levels and pre-and postoperative serum calcium levels. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Calcium level lower than 1.9 mmol/L (7.61 mg/dL) after 24 h from thyroid surgery has been reported as predictive for the development of permanent hypocalcemia.…”
Section: Introductionmentioning
confidence: 99%
“…PTC occurs in people of any age from the young to the elderly and is more prevalent in a female with a male-to-female ratio of 1:2.58 [ 3 , 4 ]. In recent years, with great advancements made in anticancer therapy, the prognosis of PTC patients has been significantly improved [ 5 ]. Nevertheless, the death rate of patients with thyroid carcinoma is still higher than that of patients with other endocrine tumors [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%